An inventory of Canadian pregnancy and birth cohort studies: research in progress - Joly Marie-Pier; Boivin Michel; Junker Anne; Bocking Alan; Kramer Michael S; Atkinson Stephanie A (BMC, 2012)
Abstract Background A web-based inventory was developed as a voluntary registry of Canadian pregnancy and birth cohort studies, with the objective to foster collaboration and sharing of research tools among cohort study groups as a means to enrich research in maternal and child health across Canada. Description Information on existing birth cohort studies conducted in Canada exclusively or as part of broader international initiatives was accessed by searching the literature in PubMed and PsychInfo databases. Additional studies were identified by enquiring about the research activities of researchers at Canadian universities or working in affiliated hospitals or research centres or institutes. Of the fifty-eight birth cohort studies initially identified, forty-six were incorporated into the inventory if they were of a retrospective and/or prospective longitudinal design and with a minimum of two phases of data collection, with the first period having occurred before, during, or shortly after pregnancy and had an initial study sample size of a minimum of 200 participants. Information collected from each study was organized into four main categories: basic information, data source and period of collection, exposures, and outcome measures and was coded and entered into an Excel spreadsheet. The information incorporated into the Excel spreadsheet was double checked, completed when necessary, and verified for completeness and accuracy by contacting the principal investigator or research coordinator. All data collected were then uploaded onto the website of the Institute of Human Development Child and Youth Health of the Canadian Institutes of Health Research. Subsequently, the database was updated and developed as an online searchable inventory on the website of the Maternal, Infant, Child and Youth Research Network. Conclusions This inventory is unique, as it represents detailed information assembled for the first time on a large number of Canadian birth cohort studies. Such information provides a valuable resource for investigators in the planning stages of cohort studies and identifying current research gaps.